2018
DOI: 10.1007/s10741-018-9738-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional abnormalities in iron-depleted heart

Abstract: Iron deficiency (ID) is a common and ominous comorbidity in heart failure (HF) and predicts worse outcomes, independently of the presence of anaemia. Accumulated data from animal models of systemic ID suggest that ID is associated with several functional and structural abnormalities of the heart. However, the exact role of myocardial iron deficiency irrespective of systemic ID and/or anaemia has been elusive. Recently, several transgenic models of cardiac-specific ID have been developed to investigate the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 75 publications
2
36
0
4
Order By: Relevance
“…Relative heart and spleen weight showed a strong positive correlation to serum transferrin levels (heart: R = 0.78, p < 0.01; spleen: R = 0.74, p < 0.01). This is in line with previous findings indicating that a Fe-deficient diet induced cardiomegaly with concomitant anemia [60] and splenomegaly in mice. [61] Interestingly, in the latter study Gibson et al [61] fed a diet with lower Fe amounts (3 mg kg −1 ) and for a longer feeding period (17 weeks) after weaning as done herein.…”
Section: Discussionsupporting
confidence: 93%
“…Relative heart and spleen weight showed a strong positive correlation to serum transferrin levels (heart: R = 0.78, p < 0.01; spleen: R = 0.74, p < 0.01). This is in line with previous findings indicating that a Fe-deficient diet induced cardiomegaly with concomitant anemia [60] and splenomegaly in mice. [61] Interestingly, in the latter study Gibson et al [61] fed a diet with lower Fe amounts (3 mg kg −1 ) and for a longer feeding period (17 weeks) after weaning as done herein.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mechanisms underlying such benefits remain controversial 7,8 . Different in vitro studies showed detrimental effects of ID on mitochondrial function among myoblasts and cardiomyocytes 9,10 . Iron treatment has been associated with improved muscular energetics in patients with HF 11 .…”
Section: Introductionmentioning
confidence: 99%
“…В связи с существенной ролью железа в многочисленных процессах (обеспечение нормальной функции клетки, энергетический обмен, передача клеточного сигнала, экспрессия генов, регуляция клеточного роста и дифференцировки [44]) в последнее время пристальное внимание уделяется изучению его содержания и функции в миокарде. На основании определения содержания железа в сердечной мышце появился даже термин «миокардиальный ЖД» (МЖД), который не всегда зависим от системного ЖД и тем более от наличия и выраженности анемии [82]. V. Melenovsky с соавт.…”
Section: патофизиологические последствия анемии и железодефицитаunclassified